Behavior of α‐synuclein–drug complexes during nanopore analysis with a superimposed AC field. Issue 2 (10th October 2016) - Jakova, Elisabet; Lee, Jeremy S.
Abstract : Seven α‐synuclein–drug complexes have been studied by nanopore analysis in which an AC field of 200 mV from 10 MHz to 1 GHz has been superimposed on the standard electrophoretic DC voltage of 100 mV. α‐Synuclein has a large dipole moment and in the absence of drug the AC field causes the molecule to oscillate at the entrance to the pore and reduces its ability to translocate through the pore. Thus more bumping events are observed in the current blockade histograms. The binding of drugs to α‐synuclein has a large effect on the event profiles depending on the region of α‐synuclein to which the drugs bind. Caffeine and (−)‐nicotine bind both the N‐ and C‐termini causing the protein to adopt a loop conformation that allows translocation even in the AC field. Metformin, which binds only to the C‐terminus also facilitates translocation. For these drugs there is good evidence that the AC field is causing the complex to dissociate as it enters the pore that has not been observed previously. In contrast, complexes with (+)‐amphetamine that has an N‐terminal binding site and cocaine that binds to the central region of the protein, show only small changes in the event profiles in an AC field.